2004
DOI: 10.1111/j.1440-1819.2003.01215.x
|View full text |Cite
|
Sign up to set email alerts
|

Premenstrual symptoms and premenstrual exacerbation in patients with psychiatric disorders

Abstract: The aim of the present study was to examine the frequencies of premenstrual syndrome (PMS) and premenstrual exacerbation (PME) of a number of psychiatric disorders in Chinese subjects. Premenstrual syndrome was assessed using a symptom checklist based on International Classification of Diseases (10th revision; ICD-10) criteria. Premenstrual exacerbation was defined as premenstrual worsening of pre-existing generalized anxiety disorder (GAD), major depressive disorder or dysthymic disorder (depressive disorders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 21 publications
4
30
0
1
Order By: Relevance
“…Symptoms of depression and anxiety disorders may increase, especially during the late luteal phase in women (Forrester-Knauss et al 2011;Pearlstein and Stone 1998). In a study conducted in China, it was shown that the premenstrual period aggravated anxiety and depressive disorders (Hsiao et al 2004). Our fi ndings are consistent with the literature.…”
Section: Resultssupporting
confidence: 91%
“…Symptoms of depression and anxiety disorders may increase, especially during the late luteal phase in women (Forrester-Knauss et al 2011;Pearlstein and Stone 1998). In a study conducted in China, it was shown that the premenstrual period aggravated anxiety and depressive disorders (Hsiao et al 2004). Our fi ndings are consistent with the literature.…”
Section: Resultssupporting
confidence: 91%
“…39 Dysthymia, MDD, panic disorder and generalized anxiety disorder are the most common axis I psychiatric disorders that may be concurrent and exacerbated premenstrually, with less clear evidence for bipolar disorder, posttraumatic stress disorder, social phobia, eating disorders and substance abuse. 12,18,[40][41][42][43] Personality disorders do not have elevated prevalence in women with PMDD, 19 but women with PMDD and a personality disorder may demonstrate premenstrual phase amplification of personality dysfunction. 44 Schizophrenia may be an example of an underlying disorder that does not have premenstrual exacerbation of psychotic symptoms but may have superimposed affective and anxiety symptoms of PMDD.…”
Section: Epidemiologymentioning
confidence: 99%
“…Previous research revealed that premenstrual symptoms were more severe among women engaged in professional studies (Marvan et al 1998); career women had more premenstrual symptoms than homemakers, and marital stress contributed to the severity of PMS symptoms (Coughlin 1990). In contrast, Hsiao (2004) and colleagues reported that no relationship was found between premenstrual symptoms and years of education or marital status.…”
Section: Sample Characteristicsmentioning
confidence: 89%